2020
DOI: 10.3390/antiox9080694
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Extract of Usnea barbata Induces Cell Killing, Apoptosis, and DNA Damage against Oral Cancer Cells through Oxidative Stress

Abstract: Some lichens provide the resources of common traditional medicines and show anticancer effects. However, the anticancer effect of Usnproliea barbata (U. barbata) is rarely investigated, especially for oral cancer cells. The aim of this study was to investigate the cell killing function of methanol extracts of U. barbata (MEUB) against oral cancer cells. MEUB shows preferential killing against a number of oral cancer cell lines (Ca9-22, OECM-1, CAL 27, HSC3, and SCC9) but rarely affects normal oral cell lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In our previous work, we clearly confirmed the direct association of oxygen radicals in gyrophoric acid-mediated DNA damage with apoptosis in HeLa cells [31]. Moreover, several studies have described DNA damage and genotoxicity caused by lichen secondary metabolites in vitro [24,41,45]. To analyze the impact of PSE-and Phy-mediated oxidative stress on DNA in Jurkat cells, DNA double-strand breaks and 8-oxoguanine formation were analyzed as biomarkers of DNA damage.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…In our previous work, we clearly confirmed the direct association of oxygen radicals in gyrophoric acid-mediated DNA damage with apoptosis in HeLa cells [31]. Moreover, several studies have described DNA damage and genotoxicity caused by lichen secondary metabolites in vitro [24,41,45]. To analyze the impact of PSE-and Phy-mediated oxidative stress on DNA in Jurkat cells, DNA double-strand breaks and 8-oxoguanine formation were analyzed as biomarkers of DNA damage.…”
Section: Resultssupporting
confidence: 72%
“…In addition, in order to determine the cytotoxic effects of PSE and Phy treatment, reactive oxygen species (ROS) were analyzed. It is known that lichen extracts and isolated/purified secondary metabolites can change the redox status of cancer cells and ROS production or accumulation, which significantly contribute to the initiation and execution of apoptosis, resulting in cytotoxicity [31,40,41]. It is also known that ROS are needed to oxidize cytochrome c, which is then capable of efficient apoptosome formation.…”
Section: Resultsmentioning
confidence: 99%
“…Wigg ( U. barbata ) is a fruticose thalli lichen with interesting therapeutic properties [ 11 ]; this species has been used for thousands of years in traditional medicine worldwide to treat various diseases [ 12 ]. The wide range of bio-activities (antioxidant [ 13 ], antimicrobial [ 14 ], anti-inflammatory [ 15 ], anticancer [ 16 ], cytotoxic [ 17 ], pro-oxidant [ 18 ]) is due to the content of active secondary metabolites [ 19 ] synthesized by the mycobiont (lichen-forming fungus) [ 20 ]. The phytochemical profile of U. barbata is already known.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have suggested that excessive production of ROS by exogenous means is more harmful to cancer cells (22). For instance, increasing ROS by exogenous drugs can cause apoptosis, DNA damage, or mitochondrial dysfunction of several cancers, including colorectal cancer, oral cancers, and breast cancer cells (44)(45)(46). We found that the effect of CVBD in inducing GBM cell apoptosis is related to the increase of intracellular ROS.…”
Section: Discussionmentioning
confidence: 59%